2006
DOI: 10.1111/j.1365-2966.2006.10746.x
|View full text |Cite
|
Sign up to set email alerts
|

XMM���Newtonobservations of the massive colliding wind binary and non-thermal radio emitter Cyg���OB2���#8A [O6If + O5.5III(f)]

Abstract: We report on the results of four XMM–Newton observations separated by about ten days from each other of Cyg OB2 #8A [O6If + O5.5III(f)]. This massive colliding wind binary is a very bright X‐ray emitter — one of the first X‐ray emitting O‐stars discovered by the Einstein satellite — as well as a confirmed non‐thermal radio emitter whose binarity was discovered quite recently. The X‐ray spectrum between 0.5 and 10.0 keV is essentially thermal, and is best fitted with a three‐component model with temperatures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(98 citation statements)
references
References 50 publications
(85 reference statements)
6
91
0
1
Order By: Relevance
“…Cyg OB2 #5 and 12 are known to vary, but unfortunately, their variations are not fully explained and predictable (Linder et al 2009;Rauw 2011). The behavior of the collidingwind binary Cyg OB2 #8A is, however, well known (De Becker et al 2006;Blomme et al 2010), and the Swift data are here fully consistent with the XMM-Newton and ASCA data, when taking the errors due to a lower number of counts in the Swift data into account. The rapid brightening of Cyg OB2 #9 near periastron, on timescales of days, may thus well be real.…”
Section: The Spectrasupporting
confidence: 76%
See 1 more Smart Citation
“…Cyg OB2 #5 and 12 are known to vary, but unfortunately, their variations are not fully explained and predictable (Linder et al 2009;Rauw 2011). The behavior of the collidingwind binary Cyg OB2 #8A is, however, well known (De Becker et al 2006;Blomme et al 2010), and the Swift data are here fully consistent with the XMM-Newton and ASCA data, when taking the errors due to a lower number of counts in the Swift data into account. The rapid brightening of Cyg OB2 #9 near periastron, on timescales of days, may thus well be real.…”
Section: The Spectrasupporting
confidence: 76%
“…γ 2 Vel and WR22 did not show any 1/D variation, despite the changing separation of their components (Rauw et al 2000b;Gosset et al 2009). Cyg OB2 #8A and WR140 deviate from expectations at periastron, since the collisions then become radiative (De Becker et al 2006;Pollock et al 2002;De Becker et al 2012). Hints of the influence of a 1/D relation may have been found in HD 93205 (see Fig.…”
Section: A Wind-wind Collision In Cyg Ob2 #9mentioning
confidence: 99%
“…This massive binary with a period of 21.908 d (De Becker et al 2004b) is one of the colliding-wind binaries with the best-constrained stellar, wind, and orbital parameters so far. It has also been intensively investigated in X-rays with a well-studied phase-locked variability (De Becker et al 2006b;Blomme et al 2010) and upper limits on the hard X-ray emission derived from INTEGRAL observations ). The detailed study by Blomme et al (2010) reported on a phasedependent radio light curve and presented some modelling of the non-thermal radio emission from Cyg OB2 #8A.…”
Section: Appendix A: the Cataloguementioning
confidence: 99%
“…Second, in a number of cases non-thermal emission is observed (e.g. Dougherty & Williams 2000;van Loo 2005;De Becker et al 2006;van Loo et al 2006van Loo et al , 2008De Becker 2007;Nazé et al 2008;Montes et al 2009;Blomme et al 2010;A&A 570, A10 (2014) A prime example that fits into this class of X-ray and nonthermal radio emitting massive binary is the O+O-star system Cyg OB2#9 (van Loo et al 2008;Nazé et al 2008Nazé et al , 2010Volpi et al 2011). Our recent campaign to study this object has so far consisted of an analysis of optical and X-ray data by Nazé et al (2012b), and radio observations by Blomme et al (2013), which have refined the orbital solution and provided initial estimates for the stellar parameters − see Tables 1 and 2.…”
Section: Introductionmentioning
confidence: 99%